LAYANAN iBIMBINGAN iKELOMPOK iDIMASA iPANDEMI iMELALUI iTEKNIK iMODELING iUNTUK iKEDISIPLINAN iSISWA iSMA iKELAS iXI - Putri Laila Qareeba; Nandang Rukanda; Tuti Alawiyah (IKIP Siliwangi, 2022)
This iresearch iis imotivated iby ithe iexistence iof istudents iwho ihave ilow idiscipline itowards ischool irules iso ithat iitibecomes ian iinteresting iproblem ifor iresearchers ito imake ias ia iresearch ititle ifor ithe ismooth iteaching iand ilearningiprocess iand istudent isuccess. iat iSMAN i1 iCiranjang iusing imodeling itechniques. iThe ipurpose iof ithis istudy iwas ito ifindiout ihow ithe iimplementation iof igroup iguidance iservices iin iimproving idiscipline ithrough imodeling itechniques iat iSMANi1 iCiranjang ischool. iSubjects iconsisting iof i7 istudents iwith idata icollection itechniques icarried iout iby iquestionnaires.iData iwere ianalyzed idescriptively iqualitatively. The iresults ishowed ithat ithe idiscipline iof iclass iXI istudents iwas iincludediin ithe igood icategory. iThus, igroup iguidance iservices ithrough imodeling itechniques ifor ithe idiscipline iof iclass iXIistudents iare ifeasible iand ican iovercome istudent idiscipline iproblems.Keywords: iGroup iguidance, imodeling itechniques, idiscipline